2007
DOI: 10.1111/j.1399-302x.2007.00332.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and serotype distribution of Actinobacillus actinomycetemcomitans in cardiovascular specimens from Japanese patients

Abstract: Actinobacillus actinomycetemcomitans, an important pathogen in periodontitis, has also been detected in cardiovascular tissues. Sixty heart valves were collected during valve replacement surgery from 60 patients (one from each), 10 were from patients with infective endocarditis (IE group) and 50 were from patients with other valvular diseases (non-IE group). In addition, 46 samples of aneurysmal tissue were taken from 46 patients with a thoracic or abdominal aneurysm (Aneurysm group, one from each). Dental pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
0
33
1
3
Order By: Relevance
“…Viable A. actinomycetemcomitans has also been isolated from atherosclerotic lesions, suggesting the periodontal pathogen is associated with the pathogenesis of this leading cause of death in the United States (20). Notably, a recent report indicated that A. actinomycetemcomitans was detected in 31% of cardiovascular specimens of endocarditis or aneurysm, using a molecular approach (24). This finding suggests that A. actinomycetemcomitans contributes to cardiovascular diseases more than was previously suggested by the blood culture data (4).…”
contrasting
confidence: 38%
See 1 more Smart Citation
“…Viable A. actinomycetemcomitans has also been isolated from atherosclerotic lesions, suggesting the periodontal pathogen is associated with the pathogenesis of this leading cause of death in the United States (20). Notably, a recent report indicated that A. actinomycetemcomitans was detected in 31% of cardiovascular specimens of endocarditis or aneurysm, using a molecular approach (24). This finding suggests that A. actinomycetemcomitans contributes to cardiovascular diseases more than was previously suggested by the blood culture data (4).…”
contrasting
confidence: 38%
“…on May 11, 2018 by guest http://iai.asm.org/ vascular diseases, including infective endocarditis (4,10,26), atherosclerosis (20), and aneurysm (24). These findings are not surprising, since periodontal pathogens can enter the bloodstream through daily activities, including tooth brushing and chewing food, especially in individuals with poor oral hygiene (12,37).…”
Section: Vol 76 2008mentioning
confidence: 93%
“…Esto puede aumentar la gravedad de la enfermedad y mantener el estado proinflamatorio. Sin embargo, la mayor铆a de estudios sobre la presencia de microorganismos periodontales pat贸genos en muestras cardiovasculares, se ha realizado en ateromas (9,11,(31)(32)(33),y en los estudios relacionados con v谩lvulas cardiacas, se han reportado principalmente pat贸genos como Streptococcus mutans (34).…”
Section: Discussionunclassified
“…The frequency and severity of bacteremia correlates with the state of the periodontal tissues. Numerous studies confirm the significance of periopathogens in atherosclerotic plaque [4]. Chronic inflammation plays an important role in the mechanisms of the development of atherosclerosis [2,5,6].…”
mentioning
confidence: 91%